Relationship On Class Management For Learning Achievements Students In Building Engineering Education Department, Faculty Of Engineering, Universitas Negeri Manado - Tumanduk, M S S S; Oroh, R R (Journal of Educational Method and Technology, 2019)
This study aims to determine whether there is a relationship between classroom management and student achievement in the Building Engineering Education Department, The Faculty of Engineering, Universitas Negeri Manado, and look for obstacles or obstacles that inhibit the success of student learning while looking for efforts to overcome these problems. This research method is correlational research. The results of a simple linear regression analysis of the variables of classroom management and student achievement in the Building Egineering Education Department, Faculty of Engineering, Universitas Negeri Manado obtained the equation of the regression line á»· = 34.80 + 0.42 X, which illustrates that if class management increases by one unit, student achievement will increase amounting to 0.361 units. Similarly, the results obtained that the regression model is good enough, because based on the model deviation test shows that the deviation is not significant at the 5% test level in this case F (Calculate) = 0.73 <F (Table) = 2.43. Thus, the regression equation above can be used to estimate or predict learning achievement (Y) if class management (X) is known. The results of testing the hypothesis, it is evident that the classroom management variables (X) have a positive and significant effect on student learning achievement at the Building Egineering Education at Universitas Negeri Manado. Based on these results, there is a significant and positive relationship between classroom management and student achievement in the Building Egineering Education Department students at Universitas Negeri Manado.Â Keywords: Classroom Management; Students; Learning Achievement